Changes in Protein Expression in Response to Heat Shock and Heat Stress in Three Tomato (Solanum lycopersicum) Landraces from Sudan - Elsharief, Aida Ali; Ahmed, Eltayeb, E.A. (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
This work was carried out to study types of proteins induced and degraded in response to heat shock treatment and at flowering stage after growth under heat stress, in three landraces of tomato ( Solanum lycopersicum) from Sudan HSD 0977, Toktuk and Abu-Zarif in relation to a heat sensitive commercial genotype Strain B. SDS PAGE method was applied for determination of proteins. Heat shock and heat stress caused degradation of some constitutive proteins and induced some HSPs, but to different extents in the studied genotypes which may indicate difference in heat tolerance. At flowering stage HSD 0977 showed the highest response against the effect of heat stress followed by Strain B this was expressed by the induction of the largest number of heat shock proteins. Toktuk and Abu-Zarif were nearly similar in their response to heat stress by induction of only three types of sHSPs which may reflect their higher thermotolerance compared to the two remaining genotypes.